Employee Engagement Practices in Organized Retail Sector: an Empirical Study with Respect to Ernakulam Town - K. Nair, Sabu; Chandrachoodan Nair, B (International Journal of Engineering and Technology, 2018)
Dynamic Employee Engagement envelops and interfaces a huge scope of administration teach which swings it to be a far reaching idea. Employee Engagement is an approach in the workplace resulting in the accurate environment for all the employees working in an organisation to voluntarily give of their best each day with the commitment towards organization’s goals and values. This paper tries to find practices of Employee Engagement prevailing within the organized retail industry in Ernakulum district. The Study has been carried out in various organised retail stores like Future - Bigbazar, Aditya Birla – More, Reliance Trends, Reliance Fresh, Reliance Foot Print & among the E retailers like Daily Fish & Fresh to Home .The survey was conducted among 50 employees from the mentioned companies in Ernakulum district. The objective of the paper is to study the Employee Engagement Practices which the organised retail Industry follows in Ernakulum district. The study examines the importance of job clarity, fun at work, work conditions, rewards &recognition, empowerment, co-worker support, commitment, passion and work Relationship. The findings of the study shows that rewards and recognition and work conditions plays a major role in employee engagement among organised retail companies which leads to increased productivity, retention, commitment and profitability.